1H NMR and 1H–13C HSQC surface characterization of chitosan–chitin sheath-core nanowhiskers. (5th June 2015) - Pereira, Antonio G.B.; Muniz, Edvani C.; Hsieh, You-Lo
Highlights: Chitosan–chitin sheath-core nanowhiskers (CsNWs) from chitin nanowhisters (CtNWs). CsNws and CtNWs surface characterization using liquid-state high-resolution NMR. Degree of acetylation at the whiskers surfaces by 1 H NMR and 1 H– 13 C HSQC spectroscopy. CsNWs presented unique 1 H NMR signals due to their crystalline structure. Abstract: Surface deacetylation of chitin nanowhiskers (CtNWs) to chitosan–sheath/chitin-core nanowhiskers (CsNWs) was successfully monitored by liquid-state high-resolution NMR of colloidal suspensions of these never-dried nanowhiskers. CtNWs were derived from acid hydrolysis (3 N HCl, 30 mL/g, 90 min, 104 °C) of chitin at 65% yield and 86% CrI . Deacetylation (50% NaOH, 48 h, 50 °C) of CtNWs generated CsNWs with unchanged nanowhisker morphology and overall length and width dimensions, but a reduced CrI of 54%. Successful step-wise exchanging the aqueous media with acetone, then D2 O prevented agglomeration of nanowhiskers and enabled NMR detection of individual nanowhiskers. The crystalline structure of CtNWs and CsNWs provided different chemical environments for the glucosamine hydrogen atom H2, splitting the NMR signals into 2 peaks ( δ 3.0 and δ 3.35 ppm) which differed from that reported for soluble chitosan ( δ 3.2 ppm). Besides, 1 H– 13 C HSQC was only possible for CsNWs indicating the NMR phenomenon observed to represent that of the surfaces where the outer layers were highly mobile and less crystalline. The degree of acetylation at the surfaces was determined from 1 H NMR data to be 56% and 9% for CtNWs and CsNWs, respectively.